Identification of Antiviral Compounds against Hepatitis C Virus (HCV) targeting NS3 Protein by Pharmacophore Modeling, Molecular Docking, and ADMET Approach - Rahayu, Ratih; Erlina, Linda; Ratnoglik, Suratno Lulut; Yasmon, Andi; Fadilah; Paramita, Rafika Indah (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Hepatitis C Virus (HCV) is a world health problem. HCV infection is initiated by various structural and non-structural proteins. The HCV NS3 protein has an important function in viral replication. The N-terminal domain of NS3 acts as a protease to process most of the viral polypeptides. NS3 also acts as an RNA helicase and NTPase and triggers liver fibrosis which accelerates the development of liver disease. Thus, this study aims to provide information on potential new antiviral candidates against HCV that target the NS3 protein. This study was conducted in-silico with a ligand-based and structure-based pharmacophore model to the cavity of the active protein site generated after virtual screening and molecular docking. The results of this study showed that three compounds, namely stigmasterol, gamma-mangostin, and erycristagallin, were found as HCV antiviral candidates that target the NS3 protein with a lower binding affinity than the native ligand. The binding energy of each compound is -9.23 Kcal/mol, -8.58 Kcal/mol, and -8.17 Kcal/mol. Based on ADMET analysis, the three compounds have high absorption in the small intestine. The cytotoxicity analysis of stigmasterol compounds is not potentially mutagenic, and the LD50 value of stigmasterol is also lower than other compounds.